Security enhancement of the phase-shifting interferometry-based cryptosystem by independent random phase modulation in each exposure. (February 2017) - Liao, Meihua; He, Wenqi; Lu, Dajiang; Wu, Jiachen; Peng, Xiang
Abstract: The traditional phase-shifting interferometry (PSI)-based cryptosystem is one of the most classical optical cryptosystems. It employs the Mach–Zahnder interferometer to record the intensity distributions to partly overcome the inconvenience while storing the complex-valued ciphertext in some other optical cryptosystems (e.g., double random phase encoding technique). However, it has been proven to be vulnerable to chosen-plaintext attack and known-plaintext attack. In this manuscript, we propose an alternative method to enhance the security strength of the traditional PSI-based cryptosystem. By substituting the fixed random phase mask (RPM) and the phase retarder in the reference arm with four independent and different RPMs (served as secret keys) in four exposures, we can correspondingly capture four intensity-only patterns (regarded as ciphertexts). Theoretical analysis, especially with respect to security characteristics, as well as the numerical simulations are presented to verify the feasibility and reliability of the proposed cryptosystem. Highlights: An alternative method to enhance the security strength of the phase-shifting interferometry-based cryptosystem is proposed. Our proposed scheme maintains the nature advantages of the traditional phase-shifting interferometry-based cryptosystem. The security analysis indicates our scheme can resist the chosen-plaintext attack and known-plaintext attack.